High Fidelity of Mouse Models Mimicking Human Genetic Skeletal Disorders - Brommage, Robert; Ohlsson, Claes (Frontiers in Endocrinology, 2020)
The 2015 International Skeletal Dysplasia Society nosology update identified 318 genes for which mutations result in rare human skeletal disorders. Together with an additional 76 genes identified by manual curation, these 394 genes code for enzymes (33%), signal transduction proteins (16%), transcription factors (15%), scaffolding proteins (15%), cilia proteins (9%), extracellular matrix proteins (6%), and membrane transporters (5%). There are 25 (6%) X-linked genes. Skeletal disorders include aggrecanopathies, channelopathies, ciliopathies, cohesinopathies, laminopathies, protein-folding defects and ribosomopathies. With the goal of evaluating the ability of mouse models to mimic these human genetic skeletal disorders, a PubMed literature search identified 259 genes for which mutant mice were examined for skeletal phenotypes. These mouse models included spontaneous and chemical-induced mutants, global and conditional gene knockouts, and transgenic mice with gene over-expression or specific base-pair substitutions. The human X-linked gene ARSE and small nuclear RNA U4ATAC, a component of the minor spliceosome, do not have mouse homologues. Mouse skeletal phenotypes mimicking human skeletal disorders were observed in 253 of the 259 genes (97%) for which comparisons were possible. Mutations in 6 mouse genes (Ccn6, Flna, Hlxb9, Lemd3, Nsd1, Smarcal1) do not result in similar skeletal phenotypes observed with mutations of the homologous human genes. These discrepancies can result from failure of mouse models to mimic the exact human gene mutations. There are no obvious commonalities among these 6 genes. Since many human genetic disorders involve hypomorphic, gain-of-function, dominant-negative and intronic mutations, future studies will undoubtedly utilize CRISPR/Cas9 technology to examine transgenic mice having genes modified to exactly mimic variant human sequences. Mutant mice will increasingly be employed for drug development studies designed to treat human genetic skeletal disorders.